Combined transcriptomics and metabolomics analyses reveal the molecular mechanism of heat tolerance in Pichia kudriavzevii - Wang, Ning; Li, Lu; Ma, Yi; Shen, Caihong; Ao, Zonghua; Song, Chuan; Mehmood, Muhammad Aamer; Zhang, Puyu; Liu, Ying; Sun, Xiaoke; Zhu, Hui (Frontiers in Microbiology, 2025)
IntroductionPichia kudriavzevii is a prevalent non-Saccharomyces cerevisiae yeast in baijiu brewing. The aim of this study was to isolate a high temperature resistant Pichia kudriavzevii strain from the daqu of strong flavor baijiu and to elucidate its molecular mechanism.MethodsGrowth activity was assessed at temperatures of 37°C, 40°C, 45°C, and 50°C. Morphological changes were observed by scanning electron microscopy at 37°C, 45°C, and 50°C. Subsequent analysis of the transcriptomics and metabolomics was undertaken to elucidate the molecular mechanism of heat tolerance.ResultsThe strain was able to tolerate high temperature of 50°C, undergoing substantial morphological alterations. Gene ontology (GO) analysis of the transcriptomics revealed that differentially expressed genes (DEGs) were enriched in pathways such as ATP biosynthesis process and mitochondrion; Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis showed that DEGs were up regulated in oxidative phosphorylation. Utilising liquid chromatograph-mass spectrometer, a total of 463 cationic differential metabolites and 352 anionic differential metabolites were detected and screened for differential substances that were closely related to heat tolerance (NAD+ and ADP); KEGG analysis showed that metabolites were up regulated in purine metabolism. Furthermore, correlation analyses of transcriptomics-metabolomics demonstrated a strong positive correlation between the metabolites NAD+ and ADP, and multiple DEGs of the oxidative phosphorylation pathway.DiscussionThese results suggest that the heat tolerant strain can be able to counteract high temperature environment by up regulating energy metabolism (especially oxidative phosphorylation) to increase ATP production.